Divide: x³ – 1 by x – 1
Answers
Answered by
9
Step-by-step explanation:
Division x^{3}x
3
+ 1 by x +1 mention in attachment
Reminder is zero
so, Put x = -1
x^{3}x
3
+ 1 =(-1)^{3} + 1 = -1+1 =0(−1)
3
+1=−1+1=0
Hence prove remainder theorem.
To learn more
i)Divide x3-1 by x-1 .verify by remainder theorem
https://brainly.in/question/10373901
ii)Using long division method show that the polynomial p(x)=x3+1 is divisible by q(x)=x+1. verify your result using factor theorem
Attachments:
![](https://hi-static.z-dn.net/files/dcd/683cd3cf17156d75593e4dfcd1e9b756.jpg)
Answered by
0
Answer:
veryfied answer
Step-by-step explanation:
PLEASE MAKE ME BRAINY
Attachments:
![](https://hi-static.z-dn.net/files/d83/e32826a268e4c3bae002360704a2d55c.jpg)
Similar questions